2015
DOI: 10.5713/ajas.15.0797
|View full text |Cite
|
Sign up to set email alerts
|

Role of Growth Differentiation Factor 9 and Bone Morphogenetic Protein 15 in Ovarian Function and Their Importance in Mammalian Female Fertility — A Review

Abstract: Growth factors play an important role during early ovarian development and folliculogenesis, since they regulate the migration of germ cells to the gonadal ridge. They also act on follicle recruitment, proliferation/atresia of granulosa cells and theca, steroidogenesis, oocyte maturation, ovulation and luteinization. Among the growth factors, the growth differentiation factor 9 (GDF9) and the bone morphogenetic protein 15 (BMP15), belong to the transforming growth factor beta (TGF-β) superfamily, have been imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 116 publications
(184 reference statements)
1
61
0
8
Order By: Relevance
“…However, PLXNA3 p.Val1238Met variant was observed in 54 out of 84,893 alleles (0.00063), BMP15 p.Arg68Trp variant in 31 out of 31,965 alleles (0.00096), ADGRD2 p.Ala630Thr variant in one out of 21,292 alleles (0.000046), and CFAP65 p.Ile1240Phe in 17 out of 11,9076 alleles (0.00014) in the ExAC database (http://exac.broadinstitute.org) suggesting that they are likely nonpathogenic. Moreover, CFAP65 was expressed in testis (Imsland et al., ), ADGRD2was an adhesion G‐protein‐coupled recently involved in absence of the vas deferens (Patat et al., ), BMP15 is involved in ovarian function (de Castro, Cruz, & Leal ), and HEPH is involved in iron metabolism (Jiang et al., ). As patient 2 had myoclonic seizures, we searched for any second variant in the 33 known genes involved in epileptic encephalopathy (Epi4K Consortium et al., ) but we did not identified de novo or inherited variant in this list of genes suggesting either the occurrence of another variant in an unknown epilepsy genes or the non‐specific epileptic status of patient 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, PLXNA3 p.Val1238Met variant was observed in 54 out of 84,893 alleles (0.00063), BMP15 p.Arg68Trp variant in 31 out of 31,965 alleles (0.00096), ADGRD2 p.Ala630Thr variant in one out of 21,292 alleles (0.000046), and CFAP65 p.Ile1240Phe in 17 out of 11,9076 alleles (0.00014) in the ExAC database (http://exac.broadinstitute.org) suggesting that they are likely nonpathogenic. Moreover, CFAP65 was expressed in testis (Imsland et al., ), ADGRD2was an adhesion G‐protein‐coupled recently involved in absence of the vas deferens (Patat et al., ), BMP15 is involved in ovarian function (de Castro, Cruz, & Leal ), and HEPH is involved in iron metabolism (Jiang et al., ). As patient 2 had myoclonic seizures, we searched for any second variant in the 33 known genes involved in epileptic encephalopathy (Epi4K Consortium et al., ) but we did not identified de novo or inherited variant in this list of genes suggesting either the occurrence of another variant in an unknown epilepsy genes or the non‐specific epileptic status of patient 2.…”
Section: Resultsmentioning
confidence: 99%
“…Among OSFs, the growth differentiation factor‐9 (GDF‐9), together with the bone morphogenetic protein‐15 (BMP‐15), is directly involved in the acquisition of oocyte developmental competence in different species. This factor is a member of the transforming growth factor‐β (TGF‐β) superfamily and it binds specifically to the BMPRII/ALK5 receptor on cumulus cells membrane, leading to several phosphorylations of intracellular signal transducer molecules (SMAD pathway) to stimulate the expression of specific target genes (de Castro, Cruz, & Leal, ). Females with mutations on GDF‐9 are affected by different reproductive disorders, as infertility, ovarian failure or reduced litter size (McNatty et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These factors are also involved in the communication among oocyte and cumulus cells, where they control the biosynthesis of cholesterol in cumulus cells, glycolysis, and absorption of amino acids. Although the mode of action has not been fully understood, in vitro studies revealed that the factors BMP15 and GDF9 stimulate the ovarian follicles growth and cumulus cells proliferation through the initiation of mitosis in cells and theca and granulosa expression of genes connected to follicular maturation (de Castro, Cruz, & Leal, 2016). Assumed that positive selection is generally linked with the branch length and rapid gene evolution and the genes related to reproduction evolve rapidly and often proved positive selection (Meslin et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The BMP15 and GDF9 contribute in the development of primary follicle from primordial follicle and play an essential role in the subsequent phases of follicular growth and maturation, enhancing the expression Cruz, & Leal, 2016). Assumed that positive selection is generally linked with the branch length and rapid gene evolution and the genes related to reproduction evolve rapidly and often proved positive selection (Meslin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation